Efektivitas Penerapan Sistem Informasi Pemerintahan Daerah terhadap Kinerja Pengelolaan Keuangan Daerah Kota Denpasar - Teken, I Ketut Aditya; romarina, arina (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2024)
This study aims to determine the effectiveness of SIPD in improving financial management performance in the Regional Finance and Asset Management Agency (BPKAD) of Denpasar City. This study used a qualitative method with a descriptive approach. Primary and secondary data were obtained through interviews, observations, documentation, and reports. The results of the study show that the application of SIPD in BPKAD Denpasar City has not been effective in improving the performance of regional financial management due to several factors, among which its application was only implemented in 2022 and requires an adaptation process for users, lack of integration with financial system data so that it requires a companion application of SIPKD for entrepreneurship, accounting, and reporting (AkLap), the system experiences frequent errors, slow application response, minimal training and socialization for users. The central government's response to the technical and operational problems faced by local governments was judged to be very slow. The study recommends enhancement of human resources capacity and competence through continuous training and socialization, data entry assistance, strengthening of communication and coordination among agencies and the central government, as well as the development of systems that are more user-friendly and integrated with other data and financial systems to become one single system sophisticated. Providing incentives and improving supporting infrastructure are critical to guarantee operational smoothness and minimize technical constraints that would hamper system performance.